HISTORICAL RELITERATION AND TRACES OF THE HERITAGE IN KUNTO DARUSSALAM KINGDOM, RIAU: RELITERASI SEJARAH DAN JEJAK PENINGGALAN KERAJAAN KUNTO DARUSSALAM, RIAU - Ellya Roza; Sukma Erni; Cut Raudhatul Miski; Afrida (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
This article aims to reliterate the history of the traces of the legacy of the Kunto Darussalam Kingdom in Riau. Exploring the past which is then manifested in various forms, both in writing and other forms will benefit society. If it hassucceeded in re-revealing the history of the region, then it can be said that the community has succeeded in repeating the history of local wisdom of the past of the community. This means that the reliteration of the history of the Kunto Darussalam Kingdom is important considering that the history of a kingdom is a symbol of the glory of the past people in its region. The method used library research method with a qualitative approach because the results are delivered in the form of strings of words and sentences. Research findings state that the Kunto Darussalam Kingdom is estimated to have been established in 1878 AD with its first king named Tengku Panglima Besar Kahar with the title Yang Dipertuan Besar (1878-1885). If you reconstruct the history of the Kunto Darussalam Kingdom, it means that you have done historical literacy. Thus, past information is not lost just like that because the reading community where it is located in general has increased its understanding of the history of the existence of the Kunto Darussalam Kingdom in Riau. The center of government of Kunto Darussalam Kingdom is Kota Lama which began with the arrival of the envoy of the Sultan of Malacca named Sultan Harimau to create a village there. Kunto Darussalam Kingdom has various relics that can still be witnessed today. For example, the palace, although the palace building is no longer the original but a duplication that has been built by the Rokan Hulu government. Likewise, the royal mosque building has undergone repeated renovations with the aim of maintenance